2017
DOI: 10.3892/ol.2017.7488
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine exerts antitumor effects on NB4 acute promyelocytic leukemia cells and functions synergistically with arsenic trioxide

Abstract: Abstract. Chloroquine (CQ) has been confirmed to exhibit antitumor effects on different types of cancer cell, but whether it exerts the same effect on acute promyelocytic leukemia (APL) cells remains to be confirmed. In the present study, the effects of various concentrations of CQ on the growth, apoptosis and cell cycle distribution ofNB4 cells, as well as the potential mechanisms underlying these effects, were examined. The combined effect of CQ and arsenic trioxide (ATO) on the growth of NB4 cells was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Western blot analysis was performed as previously reported (20). Total protein was extracted by radioimmunoprecipitation assay buffer (Sangon Biotech Co., Ltd.), and the concentration was determined by the bicinchoninic acid method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed as previously reported (20). Total protein was extracted by radioimmunoprecipitation assay buffer (Sangon Biotech Co., Ltd.), and the concentration was determined by the bicinchoninic acid method.…”
Section: Methodsmentioning
confidence: 99%
“…Cell cycle analysis was performed as previously described (20). In brief, the NCI-H209 cells transfected with NSE siRNA-1 or control siRNA for 48 h were collected and fixed with 75% ice-cold ethanol, prior to being stored at −20°C for 3 h. Subsequently, the cells were centrifuged at 7,000 g at 37°C for 1 min, resuspended in 1 ml lysis/propidium iodide (PI) buffer (0.1% Triton X-100, 0.05 mg/ml PI and 1 mg/ml RNase A; Sigma-Aldrich; Merck KGaA), incubated at 37°C for 30 min and analyzed using a FACSCanto II flow cytometer (BD Biosciences) with FACSDiva software (version 4.1; BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies provided some insight into this concern. Silencing of autophagy-related ATG5 arrested cells in S phase [33], a phenotype similar to the cells that were treated with autophagy inhibitors CQ [34], suggesting a possibility that CUR5g-induced autophagy inhibition might contribute to S phase arrest in A549 cells. It has been reported that cisplatin facilitated cell cycle arrest in lung cancer cells [35,36].…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies provided some insight into this concern. Silencing of autophagy-related ATG5 arrested cells in S phase [ 33 ], a phenotype similar to the cells that were treated with autophagy inhibitors CQ [ 34 ], suggesting a possibility that CUR5g-induced autophagy inhibition might contribute to S phase arrest in A549 cells. It has been reported that cisplatin facilitated cell cycle arrest in lung cancer cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 97%